Police involvement due to alcohol use in South Africa: results from the international alcohol control study - Londani, Mukhethwa (Acta criminologica, 2019)
In South Africa, the police are tasked with enforcing restrictions on when and where liquor may be sold, consumed and on blood alcohol concentrations (BACs) in drivers. The aim of this study was to determine the factors associated with adult drinkers’ involvement with the police due to their drinking to ascertain the characteristics of those most likely to be apprehended by the police. Data was used from the South African arm of the International Alcohol Control (IAC) Study. This study implemented multi-stage stratified cluster random sampling. The sample comprised 1 975 participants (62% males) aged 18-65 years. Factors explored included participants’ last six months’ involvement with the police due to drinking; their demographic characteristics; drinking location; type of alcohol drink consumed; diagnosis of alcohol use disorder (AUD); and perception of the police apprehending a drunk driver or someone drinking in liquor-ban areas (drinking in public places).It was revealed in the findings that alcohol-related police involvement was significantly associated with drinking spirits; and positive screening to AUD. Participants who were white were less likely to have been involved with the police due to drinking compared to those who were black African. Participants’ perception of the likelihood of a drunk driver being caught by the police was also significantly associated with their alcohol-related police. Emanating from the results it was recommended that prevention and interventions to treat people with AUDs be implemented; and that a general reduction in alcohol intake be encourage, as well as to identify and address specific risks associated with drinking spirits. These are needed to help people drink more responsibly. Efforts should also be made to increase public perception of the likelihood and consequences of drunk drivers being caught by the police.